Peran Ma’had Al-Zaytun dalam Pembentukan Sikap Toleransi Berdasarkan Pasal 29 Ayat 2 Undang-Undang Dasar 1945 dan Hukum Islam - Guntur Budi Prasetyo; Siti Ngainnur Rohmah; M. Isa Asyrofuddin (Pusat Riset dan Inovasi Nasional, 2025)
Indonesia’s diversity is a valuable asset that must be wisely managed to prevent potential conflicts. Article 29 Paragraph 2 of the 1945 Constitution guarantees freedom of religion, in line with Islamic teachings on tolerance. Ma’had Al-Zaytun serves as an example of an Islamic educational institution that instills Islamic and national values in a moderate and inclusive manner, shaping students to live harmoniously within a pluralistic society. This study aims to determine the role of Ma’had Al-Zaytun in shaping attitudes of tolerance based on Article 29 Paragraph 2 of the 1945 Constitution and Islamic Law. The research employs a descriptive approach with a library research method. Primary data were obtained from Article 29 Paragraph 2 of the 1945 Constitution and Hukum Islam by Sofyan Hasan, while secondary data were derived from journals, theses, dissertations, documents, and previous relevant studies. The results show that Ma’had Al-Zaytun plays an important role in fostering tolerance through two perspectives. Based on Article 29 Paragraph 2 of the 1945 Constitution, Al-Zaytun creates an educational environment that values diversity through curriculum design, exemplary teachers, social activities, and intercultural dialogue. From the perspective of Islamic Law, tolerance is reflected through the preservation of religion and intellect, emphasizing peace, respect for other religions, and freedom of thought and dialogue. The combination of these perspectives produces students who are religious, open-minded, and socially responsible in a pluralistic national life.